Strategi Pertahanan TNI Menghadapi Tindakan Insurjensi KKB Papua Dalam Memperkuat Pertahanan NKRI: Studi Pemanfaatan Drone Komersial - Suhirwan, Suhirwan (J-Eltrik, 2023)
This study examines the use of commercial drones by the Indonesian National Armed Forces (TNI) in countering the Armed Criminal Group (KKB) insurgency in Papua, which poses a serious challenge to national security. The deteriorating security situation in the region, demonstrated by more than 100 violent incidents in 2022, has prompted the need for innovative approaches to defense strategy. Qualitative research methods were used to explore the effectiveness and strategies for utilizing commercial drones, with data collected through literature review and thematic analysis. The results indicate that the use of commercial drones can increase intelligence accuracy by up to 30% and reduce risks to TNI personnel, despite challenges related to range and infrastructure. The study recommends the development of supporting infrastructure, ongoing training, and collaboration with technology institutions to optimize drone use. These findings provide a strategic contribution to the TNI in maintaining the sovereignty of the Unitary State of the Republic of Indonesia (NKRI) and creating stability in Papua.